1990
DOI: 10.1111/j.1365-2265.1990.tb00925.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Single‐dose Growth Hormone Therapy as an Adjuvant to Gonadotrophin Treatment for Ovulation Induction

Abstract: One intramuscular injection of biosynthetic human growth hormone (24 IU), administered on the first day of gonadotrophin treatment for ovulation induction, significantly augmented the ovarian response to gonadotrophic stimulation in seven patients. Compared with a protocol involving six injections of 24 IU of GH given on alternate days to the same patients, the smaller dose had an intermediate but highly significant effect in reducing the amount, duration of treatment and daily effective dose of hMG needed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…In fact, several studies have demonstrated that GH treatment increases ovary sensitivity to gonadotropin stimulation in infertile women with hyposensitive ovaries (12)(13)(14)(15)(16)(17)(18)(19). The effect of GH administration on gonadal function in men has been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies have demonstrated that GH treatment increases ovary sensitivity to gonadotropin stimulation in infertile women with hyposensitive ovaries (12)(13)(14)(15)(16)(17)(18)(19). The effect of GH administration on gonadal function in men has been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…At 21 days of age, MSG-treated rats received either GH or vehicle for 2 weeks. On days 21,24,28 and 31 animals were weighed and subsets were sacrificed for liver RNA extraction. The remaining animals were sacrificed at day 35 when livers and ovaries were collected, and serum was obtained for GH determinations.…”
mentioning
confidence: 99%
“…These changes were unaccompanied by changes in serum creatinine, sodium, potassium, bicarbonate, calcium or phosphate concen trations. [5] The purpose of this study was to compare the effect of a single dose of growth hormone added to hMG treat ment with that of the 6-dose protocol and with that of hMG alone.…”
Section: Resultsmentioning
confidence: 99%